A Comparative Study on the Strength Variation of Aggregate from a Selected Section of the Babai River - Tharu, Ram Kishun; Shrestha, Santosh Kumar; Shahi, Surendra Bahadur; Kafle, Mukesh (International Journal on Engineering Technology, 2025)
Large quantities of construction materials are extracted from the Babai River to meet construction needs in the Bardiya District. The primary objective of this study was to examine the various properties of riverbed aggregates and to investigate the effects of coarse aggregates and their sources on the compressive strength of concrete. For this purpose, five different sites along a 15.5 km stretch of the Babai River within the Barbardiya municipality were selected based on accessibility, extraction area, and deposition. The sample aggregates were collected following the procedure specified in IS 2430-1986, Section 3. Laboratory tests were conducted to determine the physical properties, namely specific gravity and water absorption. The results for these were in the ranges of 2.540–2.601 and 0.449–0.799%, respectively. Similarly, the Aggregate Impact Value (AIV), Aggregate Crushing Value (ACV), and Los Angeles Abrasion (LAA) values were found to be in the ranges of 6.52–10.74%, 13.45–16.24%, and 11.82–16.78%, respectively. M20 grade concrete cubes were cast using a nominal volumetric mix. The coarse aggregate source was varied, while the proportions of fine aggregate, cement, and the water-cement (w/c) ratio were held constant. The test results showed that the concrete cubes made with aggregates from the Lathuwaghat source achieved relatively higher compressive strengths, while those made with aggregates from the Babai Bridge site (near the Babai Irrigation Headworks) showed lower values at both 7 and 28 days. The findings of this study aim to provide valuable information on riverbed aggregates to local and public bodies within the construction industry.